WHO grade-specific comparative genomic hybridization pattern of astrocytoma: a meta-analysis - Holland, Heidrun; Koschny, Thomas; Ahnert, Peter; Meixensberger, Jürgen; Koschny, Ronald (Pathology, research and practice, 2010)
To detect novel genetic alterations, many astrocytomas have been investigated by comparative genomic hybridization (CGH). To identify aberration profiles characteristic of World Health Organization (WHO) grade I, II, III, and IV astrocytoma, we performed a meta-analysis of detailed genome wide CGH data of all 467 cases published so far. After expansion of all given aberrations to the maximum of 850 GTG-band resolution, the frequencies of genetic imbalances were calculated for each chromosomal band, separately for all four WHO grades. Low-grade astrocytoma has already demonstrated one characteristic of glioblastoma multiforme, gain of chromosome 7 with a hot spot at 7q32, but without loss of chromosome 10. In anaplastic astrocytoma, a more complex aberration pattern emerges from diffuse genetic imbalances. Gains of 7q32-q36 and 7p12 become the most frequent aberrations at chromosome 7. In glioblastoma multiforme, coarse aberrations like +7, −9p, −10, and −13 represent the most frequent aberrations as a characteristic pattern. In contrast to lower tumor grades, glioblastoma multiforme demonstrates +7p12 as the most frequently affected band on chromosome 7. To quantify the gradual transition from WHO grade II-IV astrocytoma, we calculated the relative increase and decrease in frequency for each detected aberration of the tumor genome. The most pronounced and diverse changes of genetic material occur at the virtual transition from low-grade to anaplastic astrocytoma. Further transition to glioblastoma multiforme is characterized by gain of 1p, chromosome 7, and loss of chromosome 10. Summing up, the expansion of the CGH results to the 850 GTG-band resolution enabled a meta-analysis to visualize WHO grade-specific aberration profiles in astrocytoma.
Gesehen am 15.03.2023